2016
DOI: 10.1016/j.exppara.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

FhCaBP1 (FH22): A Fasciola hepatica calcium-binding protein with EF-hand and dynein light chain domains

Abstract: FH22 has been previously identified as a calcium-binding protein from the common liver fluke, Fasciola hepatica. It is part of a family of at least four proteins in this organism which combine an EFhand containing N-terminal domain with a C-terminal dynein light chainlike domain. Here we report further biochemical properties of FH22, which we propose should be renamed FhCaBP1 for consistency with other family members. Molecular modelling predicted that the two domains are linked by a flexible region and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Full-length SmTAL1, a protein fragment corresponding to the EF-hand domain, four variant proteins (SmTAL1-E32A, EF-E32A, SmTAL1-D59A and EF-D59A) and a fragment corresponding to the DLC-like domain of the protein (which does not contain the EF-hand motifs required for calcium chelation), were expressed in, and purified from, E. coli (Supplementary Figure S2). These proteins were resolved under discontinuous native-PAGE and, in accordance with previous studies, the calcium-specific chelator EGTA was used to remove any endogenously bound calcium ions [10,[12][13][14][15][16]. Native-PAGE assays revealed that the electrophoretic mobility of full-length SmTAL1 was increased in the presence of EGTA (compared to untreated protein sample), whereas the addition of a molar excess of calcium ions to the EGTA-treated protein reduced the electrophoretic mobility ( Figure 2).…”
Section: Both Ef-hands In Smtal1 Interact With Calcium Ionssupporting
confidence: 66%
See 2 more Smart Citations
“…Full-length SmTAL1, a protein fragment corresponding to the EF-hand domain, four variant proteins (SmTAL1-E32A, EF-E32A, SmTAL1-D59A and EF-D59A) and a fragment corresponding to the DLC-like domain of the protein (which does not contain the EF-hand motifs required for calcium chelation), were expressed in, and purified from, E. coli (Supplementary Figure S2). These proteins were resolved under discontinuous native-PAGE and, in accordance with previous studies, the calcium-specific chelator EGTA was used to remove any endogenously bound calcium ions [10,[12][13][14][15][16]. Native-PAGE assays revealed that the electrophoretic mobility of full-length SmTAL1 was increased in the presence of EGTA (compared to untreated protein sample), whereas the addition of a molar excess of calcium ions to the EGTA-treated protein reduced the electrophoretic mobility ( Figure 2).…”
Section: Both Ef-hands In Smtal1 Interact With Calcium Ionssupporting
confidence: 66%
“…This is joined by a flexible linker to a C-terminal domain which has very high structural similarity to members of the DLC family ( Figure 1) [3][4][5]. Proteins from this family have been identified and characterised in a number of species including Schistosoma mansoni, Schistosoma japonicum, Schistosoma haematobium, Fasciola hepatica, Fasciola gigantica, Opisthorchis viverrini and Clonorchis sinensis [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In general, these proteins bind to calcium ions, although there are some exceptions, for example S. mansoni tegumental allergen-like (TAL) protein 3 (SmTAL3 or Sm20.8) [10,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous studies, the calcium chelator, EGTA, was routinely used to remove endogenously bound calcium ions from protein preparations: SmCaM proteins were then reconstituted with metal ions in a two-fold molar excess to ensure saturating binding conditions [54,[58][59][60][61][62]. For ion-binding assays, protein aliquots (10-40 µM) were incubated at 22 °C for 30 min in the presence of either EGTA, or EGTA and a two-molar excess of the appropriate ion solution, and diluted in Buffer R to a final volume of 10 µl.…”
Section: Native Gel Electrophoresismentioning
confidence: 99%
“…One family member (SmTAL3) has been identified as part of a complex which also includes a component of the microbule motor, dynein [22]. In the liver flukes Fasciola hepatica and Facsiola gigantica four members of the family have been identified and characterised [23][24][25][26][27][28][29][30]. It seems likely that further family members will be revealed in these species once their genomes are fully annotated.…”
Section: Introductionmentioning
confidence: 99%